Effect of different levels of urea treated Gamba hay on growth performance of Yankasa rams - Alli-Balogun, J. K; Abubakar, M.Y.; Abdu, S. B. (Nigerian Journal of Animal Science, 2023)
Twenty four (24) Yankasa yearling rams were used to determine the effect of feeding high levels of urea treated gamba hay (Andropogon gayanus). The rams aged 15 – 18 months with an average weight of 22 .45kg were randomly allocated to one of four dietary groups, rams in group A served as control and were offered untreated gamba hay at 2.5% of their body weight while rams in groups 2, 3 and 4 where offered 5%, 6% and 7% urea treated gamba hay respectively at 2.5% of their body weight for 90 days. All rams had equal access to water, salt lick blocks and concentrate fed at 2.0% of their body weight. Data was collected daily on feed intake, while live body weight changes and body condition score were measured weekly. Dry matter composition of the gamba hay offered declined as the level of urea treatment increased, the crude protein content of the diets also increased as the level of urea treatment increased. However the values of NDF and ADF declined as the level of urea treatment increased. Rams fed 6% and 7% treated gamba hay had significantly the highest total dry matter intake while rams fed untreated gamba hay had significantly (P<0.05) the lowest weight gain. There was no significant (P>0.05) difference in the weight gains of rams fed 6% and those fed 7% urea treated gamba hay and the rams in both groups had significantly (P<0.05) the highest weight gains. Rams fed the 6% urea treated gamba hay had the best FCR. It can be concluded that 6% &7% urea treated gamba gave similar performance but 6% had the better feed conversion ratio and is more cost effective.